Rene Girard and creative reconciliation - Ryba, Thomas, 1953- (Lexington Books, 2014)
The contribution of this book to the field of reconciliation is both theoretical and practical, recognizing that good theory guides effective practice and practice is the ground for compelling theory. Using a Girardian hermeneutic as a starting point, a new conceptual Gestalt emerges in these essays, one not fully integrated in a formal way but showing a clear understanding of some of the challenges and possibilities for dealing with the deep divisions, enmity, hatred, and other effects of violence.